Energy bill and CO2 emissions of white corn (Zea mays) production systems of Calbayog, Samar, Philippines - Archie Lauderes (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2020)
Low production in white corn is usually encountered by many farmers due to the reduction of production areas, incidence of pest and diseases, soil degradation in terms of fertility and acidity and climate change. As the world population continues to expand, there is greater pressure on resources essential for food production, including fossil energy. Hence, quest for additional calorie food sources that will require less energy and less water are needed. Data in this study were gathered using formal survey questionnaire to account the energy bill, CO2 emissions, and identify the high consuming practices in all production stages of corn. Under the farming conditions of Calbayog, Samar, at the energy audit analyses showed that white corn had 2,822.43 Mcal or 247.28 Liter Diesel Oil Equivalent (LDOE) which emits 978.12 kg of CO2 per hectare.